Fashion Law: a concept among several concepts - Bello Knoll, Susy (2023)
This paper seeks to achieve a definition of Fashion Law. For this, the author has chosen to deconstruct the different elements of the term, explaining each one of them. The deconstruction determines what is Law for the author, what is Fashion and the use of connectors. To specify the task, the Fashion industry and the meaning generated by the use of binding prepositions in the case of Fashion Law and Fashion Law are analyzed. Thoughts, definitions and opinions of the legal sector around the world are collected as an additional contribution. The conclusion provided by the explanation comes from the construction of a concept with the chosen elements of deconstruction.